Frequency and Duration Modulate Anticarcinogenic Effects of a Physical Training in the Colon - Fernandes, C.; Marini, T.; Frajacomo, F.T. T.; Jordao, A. A.; Garcia, S. B.; Kannen, V. (International Journal of Sports Medicine, 2015)
Physical exercise has proven protective against colon carcinogenesis. We sought to clarify whether the frequency and duration of physical training were key factors for its anticarcinogenic effects on the colon. Either sedentary or physically trained male Wistar rats (n=82) were either exposed or not to the carcinogen dimethylhidrazine (DMH). The first protocol investigated whether swimming for 60 min in different frequencies modulates antipreneoplastic effects of physical training. Another protocol then explored whether the duration for training 5 times a week impacts on the development of colon preneoplastic lesions. After 8 weeks, serum and colon samples were collected and analyzed afterwards. Swimming once a week for 60 min did not promote those anticarcinogenic effects found in rats trained 5 times weekly. Such weekly sustained physical training not only decreased the development of colon preneoplastic, but also epithelial proliferation, and subepithelial cyclooxygenase 2 (COX-2) expression. Interestingly, a 5 time per week training for less than 60 min was not as protective against colon carcinogenesis as swimming for 90 min. This 90 min training indeed reduced serum cholesterol and triglycerides levels, as well as colonic lipid peroxidation in carcinogen-exposed rats. Our collective data suggest anticarcinogenic effects of physical exercises are potentially promoted when training 5 times a week for at least 60 min.
Keywords: preneoplasia; carcinogenesis; physical exercise; colon cancer